2019
DOI: 10.1039/c9bm00221a
|View full text |Cite
|
Sign up to set email alerts
|

Targeted co-delivery of the aldose reductase inhibitor epalrestat and chemotherapeutic doxorubicin via a redox-sensitive prodrug approach promotes synergistic tumor suppression

Abstract: Redox responsive epalrestat prodrug micelles facilitate synergistic concentrations of doxorubicin with an advantage of CD44 down-regulation and reduced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Moreover, our study showed that the IC 50 values of ZP and EP on TNBC cell lines (BT549 and Hs578T) were almost equal to another report on the cytotoxic effect of EP on MDA-MB-231. The weak cytotoxic effect of EP is a result of slightly hydrophilic properties and a short half-life, leading to its unsuitability for use as an anticancer drug [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study showed that the IC 50 values of ZP and EP on TNBC cell lines (BT549 and Hs578T) were almost equal to another report on the cytotoxic effect of EP on MDA-MB-231. The weak cytotoxic effect of EP is a result of slightly hydrophilic properties and a short half-life, leading to its unsuitability for use as an anticancer drug [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Epalrestat is the only AKR1B1 inhibitor (ARI) that has been approved by the FDA and is used for metastatic TNBC in phase II clinical trials [ 18 ]. However, its cytotoxic effect is restricted (IC 50 value of 28.83 μg/mL on MDA-MB-231) due to its short half-life and poor hydrophilic nature [ 19 ]. Moreover, its adverse effects remain a vital problem [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the stability and avoid the premature delivery of drugs, hydrophobic drugs covalently attached to the polymer has been explored. Epalrestat and DOX were co-delivered at tumor targeted site using redox-sensitive polymer micelles composed of tocopherol polyethylene glycol succinate conjugated with vitamin B6 which acts as cancer targeted moiety [ 281 ]. Synthesized prodrug micelles disrupt in redox tumor environment of MDA MB 231 and 4T1 cell lines, and release both drugs in ratiometric manner.…”
Section: Stimuli Responsive Intelligent Nanomaterials In Cancer Thera...mentioning
confidence: 99%
“…In this regard, co‐delivery of DOX and Fidarestat has been shown to lower the MDR1, MRP1 and ABCG2 drug transporters, thereby reducing the drug efflux in tumour cells and decreasing the drug resistance 100 . Furthermore, a prodrug nano assembly of Epalrestat and DOX has increased the uptake of DOX and synergically inhibited the cell growth and improved apoptosis 101 …”
Section: Biomarker For Predictionmentioning
confidence: 99%